Independent prognostic value of ultra-sensitive quantification of tumor pre-treatment T790M subclones in EGFR mutated non-small cell lung cancer (NSCLC) treated by first/second generation TKI, depends on variant allele frequency (VAF): Results of the French cooperative thoracic intergroup (IFCT) biomarkers France project. (February 2020) - Beau-Faller, Michèle; Pencreach, Erwan; Leduc, Charlotte; Blons, Hélène; Merlio, Jean-Philippe; Bringuier, Pierre-Paul; de Fraipont, Florence; Escande, Fabienne; Lemoine, Antoinette; Ouafik, L'Houcine; Denis, Marc; Hofman, Paul; et al.
Highlights: Pre-treatment T790M mutation are detected by ddPCR in EGFR mutated NSCLC tumors. Pre-treatment T790M mutation had negative PFS value only for T790M VAF over 1%. Pre-treatment T790M mutation had negative OS value only for T790M VAF over 1%. T790M VAF is higher in cases of progressive disease under EGFR-TKI. Abstract: Objectives: T790M mutations in EGFR -mutated non-small cell lung cancer (NSCLC) account for nearly 50% of acquired resistance mechanisms to EGFR-TKIs. Earlier studies suggested that tumor T790M could also be detected in TKI-naïve EGFR -mutated NSCLC. The aim of the study is to assess the prevalence and clinical significance of quantification of tumor pre-treatment T790M subclones. Materials and methods: We analyzed 366 EGFR -mutated NSCLC patients of the real-life IFCT Biomarkers France study with available pre-treatment formalin-fixed paraffin-embedded (FFPE) tumor DNA before treatment by first/second-generation EGFR-TKI. We used ultra-sensitive Droplet Digital Polymerase Chain Reaction (ddPCR) QX200 (BIO-RAD®, Hercules, CA, USA). All samples were tested in duplicate. Results: ddPCR identified T790M in 19/240 specimens (8%). T790M-positive and T790M-negative populations were not different for clinical baseline characteristics. T790M Variant Allele Frequency (VAF) was >  0.01% <0.1%,  >  0.1% <1%,  >  1% <10%, and > 10% in five (26.3%), six (31.6%), six (31.6%), and two (10.5%) patients, respectively. T790M VAF was >0.1% in 11/13 (84%) patients with rapid (<3 months) or usual progression (3–20 months) compared to 0/3 with low progression (>20 months) ( p  = 0.02). In a Cox model, T790M mutation positivity was correlated with overall survival (OS) and progression-free survival (PFS) for 10% > VAF > 1% (hazard ratio [HR] = 2.83, 95% confidence interval [CI] 1.13–7.07, p  = 0.03; HR=3.62, 95%CI 1.43–4.92, p  = 0.007, respectively) and for VAF > 10% (HR = 19.14, 95%CI 4.35–84.26, p < 0.001; HR = 17.89, 95%CI 2.21–144.86, p  = 0.007, respectively). Conclusion: Ultra-sensitive detection of tumor T790M mutation concerned 8% of EGFR -mutated TKI-naïve NSCLC patients and has a negative prognostic value only for T790M VAF over 1%.